Etiology and Perinatal Outcome of Nonimmune Hydrops Fetalis in Southern China - He, Sheng; Wang, Linlin; Pan, Pingshan; Wei, Hongwei; Meng, Dahua; Du, Juan; Tian, Xiaoxian; Zheng, Chenguang; Qiu, Xiaoxia; Luo, Guoyang (American Journal of Perinatology Reports, 2017)
Objective This study aims to analyze the etiology and perinatal outcome of nonimmune hydrops fetalis (NIHF) in Southern China.Methods All cases with NIHF diagnosed antenatally from January 1, 2007 to December 31, 2014 were identified and analyzed.Results Total 482 cases of NIHF were identified during the study period. The most common cause of NIHF was hemoglobin (Hb) Bart's disease (61.8%), followed by chromosomal abnormalities (13.5%), idiopathic etiology (13.1%), cardiac abnormalities (6.4%), and others (5.2%). After 20 weeks' gestation, a total of 408 cases of NIHF presented, including Hb Bart's disease (279 cases), cardiac abnormalities (27 cases), and infection (7 cases). NIHF caused by chromosomal abnormalities mainly presented between 15 and 19 weeks' gestation. Of the 482 cases, 459 cases elected termination of pregnancy. The remaining 23 cases elected to continue their pregnancy. Among them, 14 (60.9%) resulted in intrauterine fetal death, 6 had neonatal death, 3 infants survived to 1 year of age. Of the three infants, one has cerebral palsy, and the remaining two are normal.Conclusions Hb Bart's disease is the most common cause of NIHF in Southern China. An effective prenatal screening and counseling program for thalassemia in this region may be the most effective way to lower the incidence NIHF.
Keywords: nonimmune hydrops fetalis; NIHF; causes; Hb Bart's disease; thalassemia